Problematics of Military Power : Government, Discipline and the Subject of Violence - Drake, Michael S. (Frank Cass, 2001)
This book traces the relations between the organization of violence and social and political order from ancient Rome to early modern Europe. Following the work of Michel Foucault, the author studies the ways authority, obedience and forms of self-conduct were produced by the micro-techniques used to govern the bodies of violence deployed in different forms of warfare.